2011
DOI: 10.1111/j.1524-4725.2011.01976.x
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Titanyl Phosphate 532-nm Laser for Treatment of a Chronic Nonhealing Exophytic Wound with Hypergranulation Tissue

Abstract: The authors have indicated no significant interest with commercial supporters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Suggested treatments include a thorough evaluation and treatment of infection, minimizing external irritation, and changing dressing types, typically to a less occlusive dressing (2). Other authors have suggested using destructive techniques such as silver nitrate, laser ablation targeted at angiogenesis, and excision (6–8).…”
Section: Discussionmentioning
confidence: 99%
“…Suggested treatments include a thorough evaluation and treatment of infection, minimizing external irritation, and changing dressing types, typically to a less occlusive dressing (2). Other authors have suggested using destructive techniques such as silver nitrate, laser ablation targeted at angiogenesis, and excision (6–8).…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 5 However, the etiology behind the development of hypergranulation tissue is not well understood. 6 Predisposing factors that have been suggested include healing by secondary intention, 7 excessive moisture, prolonged inflammation related to infection or residue dressing fibers, 8 external friction, and the repeated use of occlusive dressings. 2 Furthermore, a prolonged stimulation of fibroplasia and angiogenesis may result in the formation of hypergranulation tissue that is problematic for wound healing.…”
Section: Introductionmentioning
confidence: 99%